Is job fair still effective? - Nur Hanifah; Suhartini Suhartini (Institute of Computer Science (IOCS), 2023)
The research entitled “Job Fair Program: The Role and Influence on Recruitment Effectiveness of PT Usaha Saudara Mandiri, Tangerang, Banten” is a research on the recruitment system through the job fair conducted by PT Usaha Saudara Mandiri. Researchers carried out an internship program in the HRD-GA division of PT Usaha Saudara Mandiri and found that recruitment went through job fair get more candidates so researchers want to know how the effectiveness of this company's recruitment through the job fair program. The research method used is a qualitative method with data collection methods in the form of interviews, observation, and documentation. The method of testing the data is by reducing data, presenting data, triangulation, and drawing conclusions. The results of this study prove that there are four main aspects that make the number of applicants exceed the specified target and show the very effective recruitment of PT Usaha Saudara Mandiri through the job fair.